Analisis Pengaturan Perlindungan Hukum Keselamatan Dan Kesehatan Kerja Pada Pekerja Kurir Ekspedisi Ditinjau Dari Asas Keadilan Pancasila - Adam Ilham Fabian; Lego Karjoko; Fatma Ulfathun Najicha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Legal protection and human rights for workers are basic rights guaranteed by the constitution. The impact of the development of information technology through online buying and selling has created new jobs such as expedited couriers. However, the lack of protection, especially regarding Occupational Safety and Health (OHS), creates inequality of rights for expedition courier workers. This research aims to explore the legal protection arrangements, especially in the aspect of OHS, for expedition courier workers, with reference to the principles of Pancasila justice. The research method uses a statutory and conceptual approach, with the collection of legal materials through literature studies with legal material analysis techniques used in this legal research is deduction reasoning. The principles of Pancasila justice require regulation in accordance with the values of Pancasila. The lack of regulations covering OHS for couriers results in inequality of rights and frequent work accidents. Therefore, revision of the Occupational Safety regulation needs to be carried out by prioritizing the values of Pancasila justice to ensure the safety of workers, including expedition couriers. The government needs to review the Occupational Safety Law to cover new types of work, such as gojek and expedition services, in accordance with the justice values of Pancasila as the Ideology of the Indonesian nation